2007
DOI: 10.1080/02770900701752615
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Version of the Asthma Control Test (ACT)

Abstract: The Spanish version of ACT is shown to be a reliable and valid tool for evaluating and discriminating asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 18 publications
3
77
1
11
Order By: Relevance
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
See 1 more Smart Citation
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
“…15 The specificity is similar to a study from Korea (93%), 15 and reached a higher level than in some other countries. 7,9,13,14,16 With a cut-off point of <19, the ACT correctly predicted GINA-defined 'notcontrolled asthma' in 89% of cases while an ACT score of >20 predicted GINA-defined controlled asthma in 79% of cases. The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT.…”
Section: -9mentioning
confidence: 99%
“…[18][19][20] For children, the cACT has more validation data than other tools that target children with asthma. [37][38][39] Also, the populations used in the validation studies vary between tools.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,16 The substantially low correlations between the ACT scores and physiologic measures of asthma, such as FEV 1 values and F ENO , support the notion that asthma control cannot be inferred from physiologic measures alone. 14,17 Furthermore, the ACT has been validated in many languages [18][19][20][21][22][23] and in different settings, including in asthma specialist consultations, 9 in primary care, 13 in pharmacies, 24 by mail, 25 by speech-recognition telephone calls, 26 and over the internet. 27 …”
Section: Validitymentioning
confidence: 99%
“…Los pacientes con puntaje total menor a 20 puntos se clasifican como no controlados y aquellos con puntaje menor a 16 puntos son categorizados como pobremente controlados 10,11 . este cuestionario se ha validado en español y también ha sido replicado en nuestro medio, logrando medir con éxito el control de asma en adolescentes de 12 o más años 12,13 . el C-ACT es la versión de ACT para niños menores de 12 años.…”
Section: Cuestionarios De Control De Síntomasunclassified